'What you suggest is not what I expected': How pre-consultation expectations affect shared decision-making in patients with low back pain. (January 2023) - Kee, Karin; Gerrits, Reinie G.; de Meij, Nelleke; Boonen, Lieke H.H.M.; Willems, Paul
Abstract: Objective: Existing studies on shared decision-making (SDM) have hardly taken into consideration that patients could have independently developed expectations prior to their consultation with a healthcare provider, nor have studies explored how such expectations affect SDM. Therefore, we explore how pre-consultation expectations affect SDM in patients with low back pain. Methods: We performed a qualitative study through telephone interviews with 10 patients and seven care professionals (physicians, nurse, physician assistants) and 63 in-person observations of patient-physician consultations in an outpatient clinic in the Netherlands. Transcripts were analyzed through an open coding process. Results: A discrepancy existed between what patients expected and what care professionals could offer. Professionals perceived they had to undertake additional efforts to address patients' 'unrealistic' expectations while attempting SDM. Patients, in turn, were often dissatisfied with the outcomes of the SDM encounter, as they believed their own expectations were not reflected in the final decision. Conclusion: Unaddressed pre-consultation expectations form a barrier to constructive SDM encounters. Practical implications: Patients' pre-consultation expectations need to be explored during the SDM encounter. To achieve decisions that are truly shared by care professionals and patients, patients' pre-consultation expectations should be better incorporated into SDM models and education. Highlights: Patients may develop pre-consultation expectations about diagnosis and treatment. Unaddressed pre-consultation expectations form a barrier to shared decision-making. Patients' pre-consultation expectations should be explored during the consultation. Patients' emotions should be better incorporated in SDM models and education.